Pressure on the Danish krone in times of crisis - Asger Munch Grønlund; Lars Risbjerg (Danmarks Nationalbank, 2020)
The Danish krone was under weakening pressure in March 2020, following the outbreak of covid-19. Contrary to earlier episodes of pressure, the pressure in March 2020 was not driven by speculation about the sustainability of the Danish fixed exchange rate policy or the euro. The pressure in March was driven by the domestic insurance and pension sector and the investment fund investors, who sold kroner in response to losses on their foreign exchange assets.
Keywords: 330; Wechselkurs; Finanzkrise; Währung; Dänemark